Multiparametric Evaluation of Tetradesmus obliquus Biomass: An Integrated Approach Including Antioxidant, Nutritional, and Energy Properties - Gilvana Scoculi de Lira; Ihana Aguiar Severo; Fernando Augusto Ferraz; Iago Gomes Costa; Matheus Murmel Guimarães; Ingrid Fátima Zattoni; Luiz Fernando Bianchini; José Viriato Coelho Vargas; Dhyogo Miléo Taher; André Bellin Mariano (Microorganisms)
The microalga Tetradesmus obliquus has emerged as a promising candidate for biotechnological and industrial applications due to its rapid growth, resilience under diverse environmental conditions, and potential for bioactive compound production. This study presents a multiparametric characterization of dry T. obliquus biomass cultivated in patented industrial-scale photobioreactors, integrating thermochemical, elemental, antioxidant, and protein analyses. Proximate and ultimate analyses were conducted to assess fuel potential, revealing favorable volatile matter (VM = 64.80–72.44%) and fixed carbon (FC = 15.77–21.23%) contents. The HHV (18.32–22.75 MJ·kg−1) and LHV (16.86–21.24 MJ·kg−1) confirmed the biomass as a viable candidate for solid biofuel. The elemental composition provided the total nitrogen values, subsequently used to estimate the protein content via both the Kjeldahl and Dumas methods, with results ranging from 36.66% to 40.02%, in line with the literature. Despite the absence of detectable antioxidant activity under the tested DPPH conditions, the biomass demonstrated a robust nutritional profile and energy potential. These findings support the industrial relevance of T. obliquus biomass, particularly for applications targeting sustainable protein sources and bioenergy solutions.